Divine Beauty from A Psychological Perspective - عبير فاضل هادي الزبيدي أ.م.د.انعام داود سلوم (College of Education for Women, 2019)
This research which is entitled (Devine Beauty), aims at studying the philosophical and literary extensive visions of Andalusian poets in search of pleasure in the beauty of divine self and its impact on the formation of a philosophical frame of mind. It also attempts to investigate the aesthetic aspects that highlight the prestige and greatness and majesty of that absolute beauty. The most important conclusion of the reach is the Bany Ahmar poets use the beauty of women and the pleasure of wine as cods to reach divine beauty and get the happiness desired with the reflection of absolute beauty in a clear philosophy and thinking of the kingdom of God Almighty.